2022
DOI: 10.7554/elife.69229
|View full text |Cite
|
Sign up to set email alerts
|

Persistent cell migration emerges from a coupling between protrusion dynamics and polarized trafficking

Abstract: Migrating cells present a variety of paths, from random to highly directional ones. While random movement can be explained by basal intrinsic activity, persistent movement requires stable polarization. Here, we quantitatively address emergence of persistent migration in RPE1 cells over long timescales. By live-cell imaging and dynamic micropatterning, we demonstrate that the Nucleus-Golgi axis aligns with direction of migration leading to efficient cell movement. We show that polarized trafficking is directed … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 73 publications
0
8
0
Order By: Relevance
“…Despite the widely held notion that MTOC orientation is a key polarity cue that helps steer mesenchymal cell migration downstream of integrin-mediated signaling, membrane protrusion can also precede centrosome and Golgi reorientation during cell motility. [29,39,73] In such cases, centrosome reorientation toward the nascent lamellipodium is thought to stabilize polarized anterograde trafficking and cytoskeletal dynamics, promoting persistent migration. Acknowledging the higher front-rear polarity (centrosome orientation) and directional persistence of U-251MG cells released from fibronectin-coated micropatterns (Figure 4D; Figure S7D,E, Supporting Information), and the simultaneous lack of direct correlation between centrosome orientation and early migration (Figure S8A-C, Supporting Information), we sought to find out whether centrosome orientation correlated with directional persistence after the cells had been allowed to migrate freely.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite the widely held notion that MTOC orientation is a key polarity cue that helps steer mesenchymal cell migration downstream of integrin-mediated signaling, membrane protrusion can also precede centrosome and Golgi reorientation during cell motility. [29,39,73] In such cases, centrosome reorientation toward the nascent lamellipodium is thought to stabilize polarized anterograde trafficking and cytoskeletal dynamics, promoting persistent migration. Acknowledging the higher front-rear polarity (centrosome orientation) and directional persistence of U-251MG cells released from fibronectin-coated micropatterns (Figure 4D; Figure S7D,E, Supporting Information), and the simultaneous lack of direct correlation between centrosome orientation and early migration (Figure S8A-C, Supporting Information), we sought to find out whether centrosome orientation correlated with directional persistence after the cells had been allowed to migrate freely.…”
Section: Resultsmentioning
confidence: 99%
“…[33][34][35] In particular, the Golgi apparatus and centrosome, both of which can function as microtubuleorganizing centers (MTOC), are aligned relative to the other organelles and the leading edge of the cell. [1,[36][37][38][39] In mesenchymal cells migrating in 2D environments, the MTOC almost invariably resides in front of the nucleus and faces the leading edge of the cell. This organizes and orients the microtubule array toward the leading edge, which helps tune adhesion dynamics and supports anterograde trafficking of polarity factors, leading to persistent protrusion and migration.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The discrepancies could be attributed to a number of overlooked factors, such as the plasticity of the ECM at high strains, 6 as well as the dynamic phases of cell migration and force generation. 47 Recently, it was shown that MDA-MB-231 cells exhibit transitions between multiple migrational phenotypes. 48,49 We expect the phenotypical plasticity further contributes to variations of cellular force generated and the stress state of the ECM.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Up to now, the optogenetic approaches that have been developed to control GTPases in space and time tended to confirm the canonical picture. For example, we and others have shown that for Rac1 and Cdc42, despite of a complex cross-activation, the recruitment at the plasma membrane of minimal GEF activating domains causally induce cell protrusions 9 and migration led by the front 10 . Along the same line, optogenetic approaches to control RhoA, reviewed in 11 and 12 , have all shown a causal induction of cell retraction.…”
Section: Introductionmentioning
confidence: 91%